A network meta-analysis on the vasomodulators for portopulmonary hypertension. (14th October 2021) - Chew, N; Tan, E X; Tan, C H; Lim, W H; Xiao, J L; Chin, Y H; Syn, N; Low, T T; Wong, R; Yip, J; Siddiqui, M S; Muthiah, M
Abstract: Background: In patients with portopulmonary hypertension (PoPH) who are eligible and awaiting liver transplant, guidelines recommend lowering pulmonary pressures with vasomodulators as a bridge to transplant. However, efficacy of each vasomodulator class as a bridge to transplant remains unknown. Purpose: This review compares the use of endothelin receptor antagonists (ERA), phosphodiesterase type-5 inhibitors (PDE5-I), prostacyclin (PC) and combination therapy in its pulmonary pressure-lowering effects and pre-transplant mortality in this strictly selected subset of patients. Methods: A search conducted on Medline and Embase on articles relating to vasomodulator use in PoPH for pulmonary pressure-lowering effects and mortality. Network analysis was conducted to summarize the evidence. Surface under the cumulative ranking curve (SUCRA) was used to rank treatments. Results: Ten studies with 180 patients were included. SUCRA analysis demonstrated largest mean pulmonary artery pressure (mPAP) and pulmonary vascular resistance (PVR) lowering effects in ERA and combination therapy, followed by PDE5-I and PC. mPAP-lowering effects were largest in ERA (MD −19.440, CI: −62.280 to 23.400) and combination therapy (MD −18.223, CI: −29.677 to −6.770) when compared to PDE5-I (table 1). Pre-transplant mortality were comparable between ERA, PDE5-I and combination therapy. Both ERA (RR:0.349. CI: 0.137–0.891) and PDE5-I (RR: 0.279, CI: 0.091–0.854) had significantly lower mortality than PC (table 2). Conclusion: This meta-analysis provides preliminary evidence that ERA have shown larger pulmonary pressure-lowering effects than PDE5-I in PoPH patients who were eligible for LT. Both ERA and PDE5-I have comparable mortality outcomes, with unfavorable outcomes in PC users. Funding Acknowledgement: Type of funding sources: None.